DAMPAK PERKEMBANGAN VILLA TERHADAP KEHIDUPAN SOSIAL EKONOMI MASYARAKAT DI JALAN BAIK-BAIK SEMINYAK - Tomos Andhyka; Ida Bagus Suryawan (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2015)
ABSTRACT This study aimed to indentify the size of the impact of villa development on social economic community life’s on Jalan Baik-Baik. The period identified of villa development started from 2009-2013. Later on the three elements, community, villa management and the goverment can work together to minimize the negative impact. This study was conducted on Jalan Baik-Baik, Banjar Seminyak, Sub-distric Seminyak, Bali. The techique of collecting data in this research using observation, in-depth interview, library research, documentation and quetionnaires. To determine the sample used Slovin formula .The population taken from overall number of family card including administrative family card. So taotaled of population is 474 family card. So amound of sample used is 84 sample. The data analysis techniques in this study using analysis descriptive quantitative which assited with skala likert and continuum line. Villa developments of the year 2009-2013 experienced growth every year. Up to 2013 there are twelve new villas operating in Jalan Baik-Baik. Based on the result of the quetionnaire and the total score from all the indicators on the social aspect, the impact of villa development on social life of community in Jalan Baik-Baik are in low category with percentage 60,67%. While the result of the questionnaire and the total score from all indicators on economic aspect, the impact of villa development on economic life of the community in Jalan Baik-Baik situated on high category with percentage 71,42%.